Basinergi Mambangun Nagari: Poverty Alleviation Program Lubuk Kilangan Padang Through Optimization Of CSR Based on Forum Nagari as Minangkabau Local Wisdom - Boykhair, Albi; Sofia, Nur Lely; Aulia, Rizka; Romadhon, Fajar; Fitria, Shoimatul (Ikatan Sarjana Ekonomi Indonesia Cabang Semarang, 2022)
As a part of BUMN companies, PT Semen Padang (Persero) helps the government in order to overcome poverty problems in Indonesia, particularly in the environment around the company. PT Semen Padang (Persero) operates in the midst of the Minangkabau community and helps the community through Corporate Social Responsibility (CSR). This study aims to explore the design of the CSR program of PT Semen Padang (Persero) in alleviating poverty in the community. The method used is descriptive qualitative with the Analytic Network Process (ANP) approach and Miles & Huberman analysis. The results of the study show that CSR, which collaborates with local wisdom in carrying out assistance programs, makes the community's financial condition better. The assistance from CSR can increase household income, but it is not optimal and not evenly distributed.